2012
DOI: 10.1258/ijsa.2009.009199
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genotype distribution and risk factors for infection in women from a small municipality in north east Brazil

Abstract: In order to assess the prevalence of human papillomavirus (HPV) infection, the HPV genotypes and factors associated with infection, we conducted a population-based survey in a small municipality in north east Brazil among women aged between 12 and 49 years. A questionnaire regarding socioeconomic variables, reproductive life and sexual behaviour was used, and women were examined gynaecologically, followed by collection of vaginal lavage with saline solution for HPV DNA determination. HPV DNA was detected by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…Other studies in Brazil showed a prevalence of 42.4% for HPV 16 found in HSIL, 63.1% of cases of CIN3 and, in the rest of world, the prevalence of HPV 16 found in HSIL was around 45% [29, 36, 37]. In the agreement, other studies in Northeastern Brazil have also found HPV 16 to be the most prevalent HPV type in women with cervical lesions [14, 3134]. In contrast to our data, another study carried out in the Northeast region of Brazil found the HPV 31 to be the most prevalent among women with normal and abnormal cytological outcomes [30].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Other studies in Brazil showed a prevalence of 42.4% for HPV 16 found in HSIL, 63.1% of cases of CIN3 and, in the rest of world, the prevalence of HPV 16 found in HSIL was around 45% [29, 36, 37]. In the agreement, other studies in Northeastern Brazil have also found HPV 16 to be the most prevalent HPV type in women with cervical lesions [14, 3134]. In contrast to our data, another study carried out in the Northeast region of Brazil found the HPV 31 to be the most prevalent among women with normal and abnormal cytological outcomes [30].…”
Section: Discussionsupporting
confidence: 66%
“…In Northeastern Brazil, a number of papers have been published on HPV prevalence and type distribution among women with cytological and/or histological alterations [14,[30][31][32][33][34][35]. However, to the best of our knowledge, HPV prevalence among women with cervical lesions in the state of Sergipe, located in this region, has never been assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the midwest and northeast regions of the country, HPV 31 and HPV 33 are also reported with high frequencies. [6][7][8][9][10] In Brazil, many slaves who escaped or were released began to live in communities isolated from urban centers. These communities, which were called quilombos, still exist.…”
Section: Introductionmentioning
confidence: 99%
“…prevalence in studies conducted in Northeast Brazil, and other high risk HPV genotypes that are not in the vaccine were identified in these regions, indicating that some women's vaccines may not be able to protect against cervical cancer in particular populations [4,5].…”
Section: Página | 2946mentioning
confidence: 99%